ANALYSIS OF THE CARRYING CAPACITY OF URBAN DRAINAGE DIMENSIONS - Awliya Tribhuwana; Fathur Rohman; Ohan Farhan (Faculty of Engineering, Universitas Swadaya Gunung Jati, 2021)
The rain that fell in the city of Cirebon, especially the drainage on Jalan Pemuda, could not accommodate and drain the water so that it could create puddles on the roads and surrounding areas. Hourly rain intensity, planned flow rate and channel cross-sectional dimensions are the first steps for flood prevention. Hydrological analysis is used to calculate the discharge capacity of the drainage plan. The results were then analyzed the dimensions of the channel, the drainage ability to accommodate the falling rainwater where Qs is bigger than Qp. the channel discharge has not been able to accommodate the Q plan in the channel so that there will be a runoff of 17.759%. So to anticipate runoff, it is necessary to have a channel improvement plan of 33.477%. In addition to channel improvement solutions, arrange and define the boundaries of water storage areas by measuring and mapping boundaries and issuing regulations that prohibit or limit the construction of buildings that can reduce the ability of areas to store and absorb rainwater by referring to the basic building coefficient (KDB) permitted as stated in the RT/RW.